Activation of glutamatergic neurons in the organum vasculosum of the lamina terminalis induces thirst-driven sniffing - Wei He; Luo Shi; Ziteng Yue; Ke Zhao; Xiaoyi Wang; Kailin Wang; Xinyi Jing; Shangyu Bi; Tianjiao Deng; Xue Zhao; Xiaochen Tian; Xiangchen Ma; et al. (Cell Reports)
Summary: Sniffing is a specialized respiratory behavior that enables rodents to localize and track objects in their environment. The organum vasculosum of the lamina terminalis (OVLT) is critically involved in the regulation of thirst and water intake, yet its role in controlling thirst-driven exploratory sniffing behaviors remains unclear. This study demonstrates that hypertonic stimulation significantly increases sniffing and activates OVLT glutamatergic (OVLTGlut) neurons. Photostimulation of both OVLTGlut neurons and their axon terminals within the paraventricular nucleus of the hypothalamus (PVN) induces robust sniffing. Furthermore, ablation of PVN neurons projecting to the preBötzinger complex not only reduces the sniffing time induced by photostimulation of OVLTGlut neurons projecting to the PVN but also prolongs the drinking latency. These findings identify the OVLTGlut-PVN-preBötzinger complex circuit as a pivotal regulator of thirst-driven sniffing, providing insights into the neural mechanisms underlying thirst and exploratory behavior.